Perioperative management. Nutrition in the perioperative period - Żukowska, Magdalena; Fabian-Danielewska, Anna; Korabiusz, Katarzyna; Stecko, Monika; Wawryków, Agata (Journal of Education, Health and Sport, 2019)
The current patterns of perioperative management are subject to dynamic changes, questioning and modifying the previously used ones. In modern surgical practice, it is recommended to apply a comprehensive peri-operative care protocol to improve the results of ERAS (Enhanced Recover After Surgery) treatment. ERAS is a multidirectional path of perioperative care over a patient, used all over the world, developed by the international scientific society ERAS Society, initiated by the Danish surgeon Henrik Kehlet. This protocol aims to achieve the fastest possible recovery of the patient by minimizing metabolic stress caused by surgery, improving the healing process, reducing tissue swelling, reducing the number of postoperative complications, shortening the duration of hospitalization and reducing the cost of health care.